ELECTORAL JUSTICE FOR THE PRESIDENTIAL ELECTION: THE IMPLEMENTATION OF THE PRESIDENTIAL THRESHOLD AFTER CONSTITUTIONAL COURT OF THE REPUBLIC OF INDONESIA DECISION NUMBER 14/PUU-IX/2013 - Dian Fitri Sabrina, Rosa Ristawati (Hamdard Islamicus, 2020)
Electoral justice is part of justice in general. As intended by the Constitution, it is actually based on the concept of fairness and the social justice in the Fifth Principles of Pancasila. The Presidential Threshold is a concept that aims to propose qualified candidates for President and Vice President. The threshold has the purpose to set a limitation for the political party sitting in the parliament. The threshold requires political party or coalition of political party which have at least 25% of quota sitting in the parliament that may nominate the President and Vice President. This paper has 2 issues, notably the electoral justice in the presidential election in Indonesia and the implementation of presidential threshold in the presidential election in Indonesia after the Court Decision. To analyze the issues, this paper uses normative method. The method is by analyzing the Constitution and Laws. The results of the analysis have who that the electoral justice is very important to be achieved in the presidential election. The Court Decision Number 14/PUU-IX/2013 considered that the presidential threshold is in order to strengthen the presidential system. However, the current presidential threshold as one of the requiretment in nominating the President and Vice President is against justice. It is not supporting the electoral justice